Symptom-based Screening Versus Chest Radiography for TB Child Contacts: A Systematic Review and Meta-analysis. Issue 12 (15th July 2021) - Vasiliu, Anca; Abelman, Rebecca A.; Casenghi, Martina; Cohn, Jennifer; Bonnet, Maryline
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Accessibility to chest radiography remains a major challenge in high burden and low-income countries. The World Health Organization (WHO) guidelines acknowledge that for child contacts under 5 years, a negative symptom-based screening is sufficient to exclude active tuberculosis (TB), but in child contacts older than 5 years, a chest radiograph should be considered. We performed a systematic review and meta-analysis to assess the performance of symptom-based screening compared with chest radiography in household contacts under 15 years in low-income and middle-income countries. Methods: Screening articles published prior 1 October 2020 and data extraction were performed by 2 independent reviewers. The primary outcome was the concordance between symptom screening and chest radiography using the prevalence adjusted bias adjusted kappa coefficient (PABAK) and the proportion of asymptomatic children with negative chest radiography. The analysis was stratified by age group. Results: Of 639 identified articles, 10 were included. PABAK varied between 0.09 and 0.97 and between 0.22 and 0.98, in children less than 5 years and 5–14 years, respectively. The pooled proportion of children with both non-TB suggestive symptoms and chest radiography findings was 98.7% (96.9–99.8) in children less than 5 years and 98.1% (93.8–100) in children of age 5–14 years. Conclusions: Despite low concordance between symptom-based screening and chest radiography, most children without TB suggestive symptoms did not have chest radiography findings suggestive of TB. These results suggest that a negative symptom screening is sufficient to rule out active TB, supporting the WHO recommendation to use symptom-based screening alone when chest radiography is not available.